Estabelecimento e multiplicação in vitro de (Lecythis pisonis Cambess) - Mello, Tamyris (2018)
The species Lecythis pisonis Cambess, known popularly as sapucaia, presents great potential for ornamental use, production of nuts and wood, being indicated for reforestation as a climax species and for attracting the fauna. However, it presents low fruit production, and difficulty in obtaining and germinating the seeds, limiting the seminiferous propagation of the species. Thus, vegetative propagation in vitro is presented as a technique to be tested, since it allows pathogen free plants. Therefore, the objective of this study was to propagate in vitro L. pisonis. The study was divided into four parts: i) seminal minijardim; ii) disinfestation of the stem segments; iii) induction of shoots in vitro; and iv) in vitro rooting. For the assembly of the seminal minijardim, the two-year-old seedlings were transplanted to pots and the process of reinvigoration was done. Monthly collections were carried out and the productivity of minicepas was counted. In the development of the disinfestation protocol three experiments were carried out, where different concentrations and time of exposure to sodium hypochlorite (NaOCl) were tested, and different concentrations and method of application of amoxicillin were tested. In the shoot induction process two experiments were set up, testing different concentrations of 6-benzylaminopurine (BAP), kinetin (KIN) and WPM and MS culture media. For the rooting, different concentrations of indole-3-butyric acid (IBA) were analyzed with different exposure times at a thermal stress of 40 ° C. All experiments were conducted in a completely randomized design, analysis of variance and statistical analysis pertinent to each case. With the results obtained from the minijardim, it was possible to identify that the hottest months of the year, mainly December, were those with the highest average productivity of the minicepas, with a positive correlation of productivity with the average monthly temperature of the region. For the disinfestation of the vegetative material, the best results were immersion of the explants in 3% NaOCl and in amoxicillin ® 3000 mg L-1, for 20 minutes each. As for shoot induction, the MS medium supplemented with BAP (0.25 mg L-1 ) differed from the others, obtaining the best means in the evaluated characteristics. And the rooting occurs with IBA (1 mg L-1 ), and it is not necessary to adopt thermal stress. The in vitro propagation of sapucaia is possible with the techniques used in this work. However, it needs more studies and improvement of the techniques in the species for large-scale seedling production, besides studies on the acclimatization of the seedlings.